Analysis of Justice Values and the Psychological Impact of Rights Violations in the Film Miracle in Cell No. 7 - Azkia Maulana Febrian; Azkya Yusryya Kurnia; Dinda Yuliani; Muthia Raisya Yanwar Rahma; Salsabila Nur Faizah; Ratna Fitria (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the values of justice and the psychological impact of human rights violations as represented in the Indonesian version of the film Miracle in Cell No. 7. The film clearly depicts the systemic legal injustice faced by the protagonist, a father struggling with intellectual challenges, who becomes a victim of a biased and unfair legal system. This study uses a qualitative framework, utilizing content analysis techniques. The subjects of this study include the main character and his son, while the objects of the study are scenes, dialogues, and interactions that demonstrate values of justice, human rights violations, and psychological impacts. Data collection techniques were carried out through repeated observation of the film and literature study, while data analysis was carried out by grouping the findings into relevant themes. The results show that the film Miracle in Cell No. 7 represents the weak enforcement of legal justice, violations of the right to fair treatment, and discrimination against vulnerable groups. These violations of rights have an impact on the psychological condition of the main character in the form of trauma, anxiety, and emotional pressure, as well as causing emotional disturbances and a sense of loss in his son. This film is relevant for use as a medium for reflection in Civic Education to instill the values of justice, humanity, and the protection of human rights.